The effect of increasing V content on the structure, mechanical properties and oxidation resistance of Ti–Si–V–N films deposited by DC reactive magnetron sputtering - Fernandes, F. (2014)
FERNANDES, F. [et al.] - The effect of increasing V content on the structure, mechanical properties and oxidation resistance of Ti–Si–V–N films deposited by DC reactive magnetron sputtering. "Applied Surface Science". ISSN 0169-4332. Vol. 289 (2014) p. 114-123